2020
DOI: 10.35940/ijrte.e6408.018520
|View full text |Cite
|
Sign up to set email alerts
|

Critical Success Factors in Construction Projects

Abstract: For the successful implementation of the construction projects, researchers have tried to analyze the success factors. In the available literature, there is no clear indication to the success factors that are related to the projects related to construction. Many major construction journals were included to review the project success factors and developed a framework including six groups of independent variables, namely PRF, PMTMRF, PMRF, CLRF, CORF & EF and one dependent variable, i.e., CPS. The main purpose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In 2009, Guru attempted to put forth the perspectives of several researchers in this field and bring out the factors associated with the project manager's leadership style to impact project success profoundly. A great deal of research has been carried out on the factors affecting the success of several types of projects, including construction projects (Singh and Sharma, 2020). For example, Wang et al (2022) employed partial least squares-structural equation method (PLS-SEM) method to study the connection between key performance indicators and CSFs of megaprojects in the Chinese context.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2009, Guru attempted to put forth the perspectives of several researchers in this field and bring out the factors associated with the project manager's leadership style to impact project success profoundly. A great deal of research has been carried out on the factors affecting the success of several types of projects, including construction projects (Singh and Sharma, 2020). For example, Wang et al (2022) employed partial least squares-structural equation method (PLS-SEM) method to study the connection between key performance indicators and CSFs of megaprojects in the Chinese context.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wang et al (2022) employed partial least squares-structural equation method (PLS-SEM) method to study the connection between key performance indicators and CSFs of megaprojects in the Chinese context. Singh and Sharma (2020) examined a conceptual framework of 6 independent variables based on Punjab's construction projects and found that "project manager-related elements" had the greatest influence. In addition, Mathar et al (2020), identified factors that have an impact on Saudi Arabia's building projects' success, comparing the perceptions of consultant and contractors.…”
Section: Introductionmentioning
confidence: 99%